(untitled) (Universal International Scientific Journal, 2026)
This scientific work analyzes the socio-psychological impact of social networks on the formation of young people’s personal identity. The study used Erik Erikson’s theory of psychosocial development, James Marcia’s theory of identity statuses, Leon Festinger’s social comparison theory, and Henry Tajfel’s social identity theory as a basis. The analysis shows the dual impact of social networks: constructive (social support, self-expression, creative and professional development) and destructive (idealized images, dependence on external evaluation, cyberbullying, the difference between the virtual and real "I"). The results of the study include recommendations for improving digital literacy, developing critical thinking, and basing self-evaluation on internal values.